Light-responsive microRNA molecules in human retinal organoids are differentially regulated by distinct wavelengths of light - Canan Celiker; Kamila Weissova; Katerina Amruz Cerna; Jan Oppelt; Birthe Dorgau; Francisco Molina Gambin; Jana Sebestikova; Majlinda Lako; Evelyne Sernagor; Petra Liskova; Tomas Barta (iScience, 2023)
Summary: Cells in the human retina must rapidly adapt to constantly changing visual stimuli. This fast adaptation to varying levels and wavelengths of light helps to regulate circadian rhythms and allows for adaptation to high levels of illumination, thereby enabling the rest of the visual system to remain responsive. It has been shown that retinal microRNA (miRNA) molecules play a key role in regulating these processes. However, despite extensive research using various model organisms, light-regulated miRNAs in human retinal cells remain unknown. Here, we aim to characterize these miRNAs. We generated light-responsive human retinal organoids that express miRNA families and clusters typically found in the retina. Using an in-house developed photostimulation device, we identified a subset of light-regulated miRNAs. Importantly, we found that these miRNAs are differentially regulated by distinct wavelengths of light and have a rapid turnover, highlighting the dynamic and adaptive nature of the human retina.